(3GdYR hGdefGaY ddeLGgOjf aj SHjd Gddg HBdGJ GdMQhH hGdeOGaYs - (3GHf GdMLQj , CMeO Hf bGSe Hf CMeO Hf Gdabjg bGSe Hf GdMLQj GdCfOdSj, TgGH GdOjf,J (B1048 (3g` s
(3ChdgG (B:s
(3hHYO jbhd GdYHO GdabjQ GHQGgje Hf CMeO ef Ebdje ZQfGXg ScfG eOjfI ETHjdjg hJhdYJ HGdSaQ ai GdHMQ GdeMjW SGaQJ ajg eQGQkG s
(3Cdag HGdCYLejI GdQFjS GHQGgje Hf CMeO Hf ZGfe Hf eMehO Hf RcQjG GdCfOdSi GdeTghQ HGdQHGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs